2019
DOI: 10.5120/ijca2019919072
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Interrelationship amongst various Success Factors for Implementing Six Sigma in Indian Manufacturing SMEs

Abstract: Present research explores various critical success factors for successful implementation of six sigma methodology to Indian small medium enterprises of manufacturing sector. It further tries to study the interrelationship amongst them using ISM methodology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Sreedharan et al (2018) established them for manufacturing and service enterprises. Jha et al (2019) established CSF for LSS in Indian manufacturing companies. Sindhwani et al (2019) reported CSF when LSS is implemented with other strategies, e.g., Agile and Green.…”
Section: Critical Success Factors (Csf) For Lean Six Sigma (Lss) Using Quality 40mentioning
confidence: 99%
See 1 more Smart Citation
“…Sreedharan et al (2018) established them for manufacturing and service enterprises. Jha et al (2019) established CSF for LSS in Indian manufacturing companies. Sindhwani et al (2019) reported CSF when LSS is implemented with other strategies, e.g., Agile and Green.…”
Section: Critical Success Factors (Csf) For Lean Six Sigma (Lss) Using Quality 40mentioning
confidence: 99%
“…Sreedharan et al (2018) used TOPSIS (The Technique for Order of Preference by Similarity to Ideal Solution) methodology to establish hierarchy of critical failure (not success) factors for LSS. Jha et al (2019) established hierarchy of CSF for LSS using ISM (interpretive structural modelling) methodology. Sindhwani et al (2019) followed ISM approach to establish CSF for LSS, Agile, and Green Manufacturing system.…”
Section: Introductionmentioning
confidence: 99%